Protector an analysis of the concept and practice of loyalty in leader-led relationships within Malay society - Chandra Muzaffar 1947- (Strategic Information and Research Development Centre, 2020)
‟It is granted that there is political control and the expectation of political obedience where the loyal are rewarded and the disloyal punished. It is granted that criticism is frowned upon even in non-feudal societies. . . . But that does not mean that the attitude towards political control itself - in fact the whole attitude of leaders towards their followers and followers towards their leaders - is not the product of a certain history, of a certain tradition.ʺ In the republication of Chandra Muzaffarʹs modern classic, he breaks down the idea of being a ‟protectorʺ in both traditional and contemporary Malay society, analysing the dimensions of symbolic and substantive protectors. Examining the various forms of power held by the Sultans and the class of late-colonial era ‟administocratsʺ that replaced them in the post-independence period, as well as the economic and political consequences for broader Malaysian society. First published in 1979, and building on the pioneering work of Syed Hussein Alatas, this short volume remains essential reading today.